Chemostratigraphy and 40Ar/39Ar geochronology of Ventotene volcano (Pontian Islands, Tyrrhenian Sea): The missing link in the Quaternary potassic magmatism of central Italy - G.L. Cardello; A.M. Conte; M. Gaeta; B. Jicha; F. Lombardi; L. Monaco; S. Nomade; C. Perinelli; M. Petrelli; G. Sottili; D.M. Palladino (Quaternary Science Reviews, 2026)

High-temperature episyenites from late-Variscan Sàrrabus pluton (SE Sardinia, Italy) - F. Secchi; S. Naitza; A.M. Conte; G. Oggiano; M. Casalini; M. Kohút; T. Giovanardi (Lithos, 2026)

Near-term extrauterine pregnancy secondary to uterine rupture in a mare - V Palmieri; G Catone; A Conte; T Di Palma; P Liguori; I Izzo; C Vullo (Journal of Equine Veterinary Science, 2026)

Quantification of leaf photosynthetic traits in field conditions: Towards an efficient and reliable method for plant phenotyping and modelling ecophysiological processes - A. Conte; A. Carli; M. Haworth; G. Marino; V. Montesano; D. Danzi; G. Atzori; A.P.M. Fabbri; A. Daccache; R.M. Balestrini; M. Centritto (Agricultural and Forest Meteorology, 2026)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

Hazardous element inertisation in vitrified silicate ceramics: Effect of different matrices - S. Conte; C. Molinari; M. Ardit; L. Mantovani; M. Tribaudino; G. Cruciani; M. Dondi; C. Zanelli (Journal of Hazardous Materials, 2024)

Performance of Hermetia illucens (Diptera: Stratiomyidae) larvae reared on organic waste diets and pupal chitin and chitosan yield - Christina Adamaki-Sotiraki; Linda Abenaim; Alessia Mannucci; Christos I. Rumbos; Stefano Bedini; Antonella Castagna; Giuseppe Conte; Monica Tognocchi; Victor Dolianitis; Christos G. Athanassiou; Barbara Conti (Environmental Science and Pollution Research, 2024)

New evidence of the Green Tuff deposits and post-caldera, recent explosive volcanic activity at Pantelleria volcano (Sicily Channel, Italy) recorded in near-vent marine areas - C. Romagnoli; C. Giglio; A.M. Conte; A. Cloke-Hayes; M. Garcia; G. Gasparotto; S. Benetti (Journal of Volcanology and Geothermal Research, 2024)

Exploring high hydrostatic pressure for enhancing the preservation of white and dark muscle fish fillets stored at different packaging systems under refrigeration - Maria Lúcia G. Monteiro; Denes K.A. Rosário; Luiz Torres Neto; Carlos A. Conte-Junior (Food Control, 2024)

Correction to: Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)

Protecting pollinators and our food supply: understanding and managing threats to pollinator health - H. Siviter; A. Fisher; B. Baer; M. J. F. Brown; I. F. Camargo; J. Cole; Y. Le Conte; B. Dorin; J. D. Evans; W. Farina; J. Fine; L. R. Fischer; et al. (Insectes Sociaux, 2023)
Global pollinator declines threaten food production and natural ecosystems. The drivers of declines are complicated and driven by numerous factors such as pesticide use, loss of habitat, rising pathogens due to commercial bee keeping and climate change. Halting and reversing pollinator declines will require a multidisciplinary approach and international cooperation. Here, we summarize 20 presentations given in the symposium ‘Protecting pollinators and our food supply: Understanding and managing threats to pollinator health’ at the 19th Congress of the International Union for the Study of Social Insects in San Diego, 2022. We then synthesize the key findings and discuss future research areas such as better understanding the impact of anthropogenic stressors on wild bees.

Nature-based solutions for nutrient pollution control in European agricultural regions: A literature review - A. Rizzo; C. Sarti; A. Nardini; G. Conte; F. Masi; A. Pistocchi (Ecological Engineering, 2023)

Relationships between benthic infauna and groundwater eutrophication on a sandy beach in southern Brazil - Luciano Lorenzi; Devon Gebauer Mayer; Bruna Conte Reginato; Paulo Roberto Pagliosa; David Valença Dantas; Eduardo Gentil; Vladimir G. Toro Valencia (Environmental Science and Pollution Research, 2022)

Micro-climatic investigation and particulate detection in indoor environments: the case of the historical museum of Bersaglieri in Rome - A. Marcelli; M. Sebastianelli; A. Conte; F. Lucci; G. Della Ventura (Rendiconti Lincei. Scienze Fisiche e Naturali, 2020)

Type three secretion system in Salmonella Typhimurium: the key to infection - Anamaria M. P. dos Santos; Rafaela G. Ferrari; Carlos A. Conte-Junior (Genes & Genomics, 2020)

Correction to: Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Virulence Factors in Salmonella Typhimurium: The Sagacity of a Bacterium - Anamaria M. P. dos Santos; Rafaela G. Ferrari; Carlos A. Conte-Junior (Current Microbiology, 2019)

Inert gas narcosis in scuba diving, different gases different reactions - Monica Rocco; P. Pelaia; P. Di Benedetto; G. Conte; L. Maggi; S. Fiorelli; M. Mercieri; C. Balestra; R. A. De Blasi (European Journal of Applied Physiology, 2019)

Preslaughter Anesthesia with Lippia alba Essential Oil Delays the Spoilage of Chilled Rhamdia quelen - Juliana C. Veit; Jaqueline Piccolo; Aline F. Scherer; Isadora S. Machado; Luana H. Maurer; Lisiane Conte; Bernardo Baldisserotto; Gessi Koakoski; Charlene C. Menezes; Vania L. Loro; Leonardo J. G. Barcellos; Berta M. Heinzmann; et al. (Journal of Aquatic Food Product Technology, 2018)

Dentatorubro-Pallidoluysian Atrophy (DRPLA) among 700 Families with Ataxia in Brazil - Pedro Braga-Neto; José Luiz Pedroso; Gabriel Vasata Furtado; Tailise Conte Gheno; Maria Luiza Saraiva-Pereira; Laura Bannach Jardim; Orlando G. P. Barsottini (The Cerebellum, 2017)

Flower scent bouquet variation and bee pollinator visits in Stevia rebaudiana Bertoni (Asteraceae), a source of natural sweeteners - Giovanni Benelli; Angelo Canale; Donato Romano; Guido Flamini; Silvia Tavarini; Andrea Martini; Roberta Ascrizzi; Giuseppe Conte; Marcello Mele; Luciana G. Angelini (Arthropod-Plant Interactions, 2017)

In situ remediation of contaminated marinesediment: an overview - G. Lofrano; G. Libralato; D. Minetto; S. De Gisi; F. Todaro; B. Conte; D. Calabrò; L. Quatraro; M. Notarnicola (Environmental Science and Pollution Research, 2017)

Is there an association between prior anti-inflammatory drug exposure and occurrence of peritonsillar abscess (PTA)? A national multicenter prospective observational case–control study - D. Lepelletier; V. Pinaud; P. Le Conte; C. Bourigault; N. Asseray; F. Ballereau; J. Caillon; C. Ferron; C. Righini; E. Batard; G. Potel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Peritonsillar abscess (PTA): clinical characteristics, microbiology, drug exposures and outcomes of a large multicenter cohort survey of 412 patients hospitalized in 13 French university hospitals - D. Lepelletier; V. Pinaud; P. Le Conte; C. Bourigault; N. Asseray; F. Ballereau; J. Caillon; C. Ferron; C. Righini; E. Batard; G. Potel (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

A mouse informatics platform for phenotypic and translational discovery - Natalie Ring; Terrence F. Meehan; Andrew Blake; James Brown; Chao-Kung Chen; Nathalie Conte; Armida Di Fenza; Tanja Fiegel; Neil Horner; Julius O. B. Jacobsen; Natasha Karp; Thomas Lawson; et al. (Mammalian Genome, 2015)

The antiatherogenic effect of bixin in hypercholesterolemic rabbits is associated to the improvement of lipid profile and to its antioxidant and anti-inflammatory effects - Sabrina Somacal; Cassieli G. Figueiredo; Andréia Quatrin; Amanda R. Ruviaro; Lisiane Conte; Paula R. Augusti; Miguel Roehrs; Ione T. Denardin; Jocieli Kasten; Marcelo L. da Veiga; Marta M. F. Duarte; Tatiana Emanuelli (Molecular and Cellular Biochemistry, 2015)

Effect of pruning-derived biochar on heavy metals removal and water dynamics - Antonio G. Caporale; Massimo Pigna; Alessia Sommella; Pellegrino Conte (Biology and Fertility of Soils, 2014)

Classification of the geographical origin of Italian donkey's milk based on differences in inorganic anions - G. Di Bella; V. Lo Turco; A.G. Potortì; R.R. Luppino; V. Fotia; F. Conte; G. mo Dugo (Food Additives & Contaminants: Part A, 2012)

Correlation between cortical plasticity, motor learning and BDNF genotype in healthy subjects - P. Li Voti; A. Conte; A. Suppa; E. Iezzi; M. Bologna; M. S. Aniello; G. Defazio; J. C. Rothwell; Alfredo Berardelli (Experimental Brain Research, 2011)

Survey of the presence of patulin in fruit juices - E. Bonerba; E. Ceci; R. Conte; G. Tantillo (Food Additives & Contaminants Part B-Surveillance, 2010)

Isolation and characterization of polymorphic microsatellites for the natural populations of barker frog Physalaemus cuvieri - M. Conte; L. J. Cançado; P. R. Laborda; M. I. Zucchi; G. V. Andrade; D. C. Rossa-Feres; S. Siqueira; A. P. Souza; S. M. Recco-Pimentel (Conservation Genetics, 2009)

Determination of polycyclic aromatic hydrocarbons (PAHs) in commonly consumed Nigerian smoked/grilled fish and meat - V.O.E. Akpambang; G. Purcaro; L. Lajide; I.A. Amoo; L.S. Conte; S. Moret (Food Additives & Contaminants: Part A, 2009)

Organochlorine pesticides and polychlorinated biphenyl residues in reared and wild Dicentrarchus labrax from the Mediterranean Sea (Sicily, Italy) - V. Lo Turco; G. Di Bella; L. La Pera; F. Conte; B. Macrí; G. mo Dugo (Environmental Monitoring and Assessment, 2007)

The “in situ” expression of Human Leukocyte Antigen Class I antigens is not altered by cryopreservation in human arterial allografts - G. Pasquinelli; M. P. Pistillo; F. Ricci; M. Buzzi; P. L. Tazzari; L. Foroni; C. Manferdini; C. Ceccarelli; A. Stella; R. Conte (Cell and Tissue Banking, 2007)

Molecular evidence for hybrid origin of Quercus crenata Lam. (Fagaceae) from Q. cerris L. and Q. suber L. - L. Conte; C. Cotti; G. Cristofolini (Plant Biosystems, 2007)

Antiinflammatory effects of natural tetranortriterpenoids isolated from Carapa guianensis Aublet on zymosan-induced arthritis in mice - C. Penido; F. P. Conte; M. S. S. Chagas; C. A. B. Rodrigues; J. F. G. Pereira; M. G. M. O. Henriques (Inflammation Research, 2006)

1,25-dihydroxyvitamin D3 protects human pancreatic islets against cytokine-induced apoptosis via down-regulation of the fas receptor - R. Riachy; B. Vandewalle; E. Moerman; S. Belaich; B. Lukowiak; V. Gmyr; G. Muharram; J. Kerr Conte; F. Pattou (Apoptosis, 2006)

Worker-worker inhibition of honey bee behavioural development independent of queen and brood - I. Leoncini; D. Crauser; G. E. Robinson; Y. Le Conte (Insectes Sociaux, 2004)

Detection of ephemeral genetic sub-structure in the narrow endemic Abies nebrodensis (Lojac.) Mattei (Pinaceae) using RAPD markers - L Conte; C Cotti; R Schicchi; FM Raimondo; G Cristofolini (Plant Biosystems, 2004)

Research on Bacteraemia in Cultured Rainbow Trout - A. Panebianco; A. Giuffrida; F. Conte; G. Ziino; A. Minniti; L. Iannuzzi (Veterinary Research Communications, 2004)

Animal Transmissible Spongiform Encephalopathies and Genetics - U. Agrimi; M. Conte; L. Morelli; M.A. Di Bari; G. Di Guardo; C. Ligios; G. Antonucci; G.M. Aufiero; N. Pozzato; F. Mutinelli; R. Nonno; G. Vaccari (Veterinary Research Communications, 2003)

Severe 5-fluorouracil toxicity associated with a marked alteration of pharmacokinetics of 5-fluorouracil and its catabolite 5-fluoro-5,6-dihydrouracil: a case report - Bocci G.; Danesi R.; Allegrini G.; Innocenti F.; A. Di Paolo; Falcone A.; Conte P.; M. Del Tacca (European Journal of Clinical Pharmacology, 2002)

Genetic diversity in Cytisus aeolicus Guss. ( Leguminosae ), a rare endemite of the Italian flora - L. CONTE; A. TROÍA; G. CRISTOFOLINI (Plant Biosystems, 1998)

Bactericidal effect of pefloxacin and fosfomycin againstPseudomonas aeruginosa in a rabbit endocarditis model with pharmacokinetics of pefloxacin in humans simulated in vivo - D. Bugnon; G. Potel; Y. Q. Xiong; J. Caillon; D. Navas; C. Gras; M. F. Kergueris; P. Le Conte; F. Jehl; D. Baron; H. Drugeon (European Journal of Clinical Microbiology & Infectious Diseases, 1997)

Isolation and biodiversity in Cytisus villosus Pourret (Fabaceae, Genisteae): enzyme polymorphism in disjunct populations - A. TROÍA; L. CONTE; G. CRISTOFOLINI (Plant Biosystems, 1997)